KNOWLEDGE MANAGEMENT – DEVELOPMENT POTENTIAL OF TOURISM IN VOJVODINA (Heritage, 2021)
In modern tourism development, destinations are treated as tourism products that successfully compete in the market thanks to their attractive and highly competitive elements. The destination brand demonstrates the location, attractions and activities within the borders. Creating a brand is a long process, and an established brand is kept in the minds of consumers for a very long time. Therefore, it is necessary to have a long-term vision of the destination brand based on the knowledge and cooperation of all those involved in creating a tourism product. The created destination brand that is successfully represented by the relevant market segments through communication channels becomes a powerful tool in gaining and attracting market demand. Therefore, the aim of this paper is to analyze Vojvodina as a multicultural tourist destination and point out how recognizable it is as such a brand in the tourism business. The main goal is to look at the situation and perspectives for placing products on the domestic, and especially on the international tourist market. The ultimate goal is to include experts from this field and the local population in the project of developing the brand of Vojvodina tourism, in order to revive abandoned rural places, preserve the villages and tradition.
Keywords: knowledge management, multiculturalism, Vojvodina, tourist destination